Participation of Rac GTPase activating proteins in the deactivation of the phagocytic NADPH oxidase - Moskwa, Patryk; Dagher, Marie-Claire; Paclet, Marie-Hélène; Morel, Francoise; Ligeti, Erzsébet (Biochemistry (Easton), 2002)
The aim of the present study was to investigate possible mechanisms that could be involved in the deactivation of the assembled, catalytically active NADPH oxidase of phagocytic cells and thereby lead to termination of O(2)(.-) production. Our major findings are the following: (1) Addition of GDP to the active oxidase is able to reduce O(2)(.-) production both in the fully purified and in a semi-recombinant cell-free activation system. (2) p67(phox) inhibits GTP hydrolysis on Rac whereas p47(phox) has no effect on Rac GTPase activity. (3) Soluble regulatory proteins (GTPase activating protein, guanine nucleotide dissociation inhibitor, and the Rac-binding domain of the target protein p21-activated kinase) inhibit activation of the NADPH oxidase but have no effect on electron transfer via the assembled enzyme complex. (4) Membrane-associated GTPase activating proteins (GAPs) have access also to the assembled, catalytically active oxidase. Taken together, we propose that the GTP-bound active form of Rac is required for sustained enzyme activity and that membrane-localized GAPs have a role in the deactivation of NADPH oxidase.